Knowledge and perception on sepsis in Lima settlers, Peru during COVID-19 pandemic - Sánchez, Diana (2023)
Objective: To determine the level of knowledge and perception of settlers of Lima, Peru on sepsis during the COVID-19 pandemic. Methods: A cross-sectional study was carried-out using electronic survey among Lima settlers above 18 years of age from December 2020 and April 2021. We excluded health care workers. Results: 289 surveys were conducted; mean age of participants was 38±15 years; 63% were females; 64% had heard about sepsis; 63% had the perception that sepsis was potentially lethal; 18% did not know about it; 8% said that it is a severe inflammation and 7% responded that it is an allergic reaction. Fifty three percent did not know that COVID-19 could lead to sepsis but 68% knew that sepsis may cause mortality. Conclusion: The most common perception on sepsis by Lima settlers was of an infection potentially lethal, but more than half of participants did not know that COVID-19 could lead to sepsis.